College Motivation in Pursuing of E-Sport Games - Afriyuandi, Asep Ramdan; Kurniawan Pratama, Andi; Rahadian, Adi (Universitas Suryakancana, 2021)
This research aims to determine the students' motives in pursuing e-sport games. The research method used is a quantitative method with a descriptive approach. The sampling technique in this research used a purposive sampling technique with a total of 50 students at Suryakancana University, and used a questionnaire instrument with the motives of students pursuing e-sport games. The results obtained are 23% motives for spending time, 22% motives for seeking information, 21% motives for interpersonal relationships, 20% motives for convenience, and 15% motives for entertainment. It is recommended for students to make university education a top priority and not to make e-sport games an obstacle to keep achieving at university. E-sports competitions in Indonesia are often held, especially at the student level. With more frequent competitions to encourage students to excel.Key words: motives, students, e-sport games.